ENGLISH TEACHER PERSPECTIVE ON LEARNING ENGLISH AT SMA KARTIKA VIII-1 SOUTH JAKARTA - Sjafty Nursitti NP Maili; Endang Sondari (BASIS (Bahasa dan Sastra Inggris), 2020)
The objective of this study is to describe the perspective of English teachers about the 2013 curriculum, the implementation of English learning, the expectations of English teachers about the learning English. This research has been conducted at SMA Kartika VIII-1 Srengseng Sawah Jakarta Selatan It was a qualitative research that the researcher described the phenomenon happened and analysis it. The data was obtained by observation and interview. There are some steps as follow; First, Observation. It was done when the English teacher teach to the students; Second, Interview. It was taken when the English teacher taking a rest. The result of this research as follow: 1. The English teachers perspective about the concept of 2013 curriculum are positive; 2. The English teachers perspective about the implementation of learning English based on the 2013 curriculum was not maximal because there is no correspondence between the hours only 2 hours and the material taught by the English teacher; 3. English teachers expectation of learning English that is a change from 2 hours a week to 4 hours in a week.